MENINGKATKAN MOTIVASI MEMBACA MELALUI METODE BERMAIN PERAN PADA ANAK KESULITAN BELAJAR - Sarini Ramadani, Yosfan Azwandi, Martias. Z (Jurnal Penelitian Pendidikan Khusus, 2013)
This research is backgrounded by a problem of a child with reading difficulties at fourth class in SLB Bhayangkari Lintau Buo. The child felt boring to meet a lesson texts; one of them is Indonesian. Intended thing was child motivation in reading. The research using Quasi Experiment design of one group pretest-posttest which experiment was executed in one group without using compared group. Subject of the research was four of student with in reading difficulties. Data was obtained with using observation and interview. The instrument was tried out at SLB Bhayangkari Lintau Buo.